PENGARUH INFLASI, NILAI TUKAR RUPIAH, BI RATE TERHADAP NILAI AKTIVA BERSIH REKSA DANA TERPROTEKSI SYARIAH PERIODE 2014-2018 DI INDONESIA - Mohammad Ilyas; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The Research aims to determine the influence of inflation, currency exchange rate, interest rate that affect net asset value of protected Islamic mutual fund from 2014-2018 in Indonesia partially and simultaneously. The research also uses quantitative approach and multiple regression analysis technique. The sample used for this research is obtained from monthly statistic data of Bank Indonesia, Otoritas Jasa Keuangan, and Pusat data kontan which had been published online from January 2014 to Desember 2018, so there are 60 samples taken for this reserch. The variabels of this research include inflation (X1), currency exchange rate (X2), interest rate (X3), and net asset value of protected Islamic mutual fund (Y). The result of this research shows that partially, the inflation affect Net Asset Value of Protected Islamic Mutual Fund from 2014-2018 in Indonesia insignificantly, currency exchange rate affect Net Asset Value of Protected Islamic Mutual Fund from 2014-2018 in Indonesia significantly, and interest rate affect Net Asset Value of Protected Islamic Mutual Fund from 2014-2018 in Indonesia significantly. Simultaneously, all independent variables affect Net Asset Value of Protected Islamic Mutual Fund from 2014-2018 in Indonesia significantly.Keywords: Macroeconomic, Inflation, InterestRate, Currency Exchange Rate, Net Asset Value, Protected Islamic Mutual FundREFFERENCESAchsien, Iggi H. 2000. Investasi Syariah di Pasar Modal, Menggagas konsep dan Praktek portofolio Syariah. Jakarta: Gramedia Pustaka Utama.Anshori, Muslich, Sri Iswati. 2009. Metode Penelitian Kuantitatif. Cetakan Pertama. Surabaya: Universitas Airlangga press.Farid, Muhammad. 2014. Mekanisme dan Perkembangan Reksadana Syariah.Iqtishoduna Vol. 4 No. 1. Hlm. 61-72.Karl, E. Case, dan Fair, C. Rai. 2001. Prinsip-Prinsip Ekonomi Makro. Jakarta: Prenhalindo.Mankiw, Gregory. 2006. Pengantar Ekonomi Makro. Edisi Ketiga. Jakarta: Salemba Empat.Nandari, Herlina Utami Dwi Ratna Ayu. 20017. Pengaruh Inflasi, Kurs dan BI Rate Terhadap Nilai Aktiva Bersih (NAB) Reksadana  Syariah di Indonesia (Periode 2010-2016).An-Nisba Vol. 04 No. 01. Hlm. 52-73.Pilbeam, Keith. 2006. International Finance.3rd Edition. New York.Prasetyo, Bambang dan Lina MiftahulJannah. 2012. Metode Penelitian Kuantitatif. Jakarta: PT. Raja Grafindo Persada.Rahmawati, Yuke. 2009. Resolusi Investasi Keuangan Syariah. Jurnal Al-Iqtishad Vol. 1 No. 1. Hlm. 65-78.Rudiyanto. 2011. Reksa Dana untuk Pemula. Jakarta: Elex media KomputindoSudarsono, Heri. 2007. Bank dan Lembaga Keuangan Syariah (Deskripsi dan Ilustrasi). Edisi Kedua. Yogyakarta: Ekonisia.Sugiyono. 2011. Metode Penelitian Kuantitatif, Kualitatif dan R&D. Edisi Kedua Belas. Bandung: Alfabeta.Suharyadi dan Purwanto, S. K. 2004. Statistika Dasar. Jakarta: Salemba Empat.Sukirno, Sadono. 2002. Pengantar Teori Makro Ekonomi. Edisi Kedua. Jakarta: PT Raja Grafindo Persada.Sukirno, Sadono. 2006. Makro Ekonomi Teori Pengantar. Edisi Ketiga. Jakarta: PT Raja Grafindo Persada.Susanto, Burhanuddin. 2008. Hukum Perbankan Syariah di Indonesia. UII Press. Yogyakarta.Zakariya, Mukhamad. 2017. Pertumbuhan Lembaga ReksadanaSyariah di Indonesia. JES Vol. 1 No. 2. Hlm.276-285.